(untitled) (UNED Research Journal, 2015)
Personal satisfaction is an indicator of life quality. Labor and country conditions have their effect, but individual factors dominate satisfaction, including family, sex life, educational level and neighborhood. I surveyed 1000 staff members of a Costa Rican public university via email. The questionnaire considered satisfaction in the personal, labor and country level. I found no gender diference in the answers, but partnered people are more satis ed that divorcees and widowers. People with steady jobs and mature age are more satis ed. Important job factors are working schedule, amount of work, salary, infrastructure and interpersonal relationships. Life satisfaction results from the interaction of the above variables, not from a single factor.